(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Teachers are increasingly interested in using games as part of their everyday teaching practices due to the imminent promise of promoting both motivation and successful learning. However, in order to reach this goal, you need both a thorough knowledge of games and a wide breadth of experience. In this paper, we will introduce several game definitions and game categori- sation systems that will help you consider the selection criteria of the games best suited to your goals and participants. The methods used to introduce the game elements determine whether the students think it a playful task, an educational game, or a simple activity. It is vital to think it over from both the motivation and success points of view. Next, we present a collection of board games intended to develop mother tongue, linguistic ability, and other skills. Their uses have all been assigned pedagogical aspects. Getting to know many kinds of games – it is hoped – will help teachers not only to integrate them into their everyday practices but also to creati- vely re-constitute them, i.e. gamify the school tasks/exercises.